DS 95: Proceedings of the 21st International Conference on Engineering and Product Design Education (E&PDE 2019), Universit 2019
DOI: 10.35199/epde2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Comparing different types of professional practitioner engagement in an Integrated Design Engineering degree

Abstract: Design engineering education needs to be close to industrial practice, since industry is the final destination of most graduates. For this reason, early engagement with 'real' practitioners can be beneficial to educational outcomes. Although much research has been done comparing the skills and approaches of engineering design students and professional practitioners little research to date has looked in detail how this engagement affects the educational process. In this study, we evaluate the impact professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The design tutorial pedagogy has recently become more common in engineering design education, but most publications focus on describing specific implementations (e.g., Tavakoli (2000), Thompson (2002), and Vrcelj and Attard (2007)). Little research to date has looked in detail at how the engagement of practitioners affects student learning (e.g., Georgilas et al (2019)). Practitioners may not be familiar with expectations of design courses, for example they may expect complete designs (Tocco and Mata, 2012).…”
Section: Practitioner Tutors In the Design Studiomentioning
confidence: 99%
“…The design tutorial pedagogy has recently become more common in engineering design education, but most publications focus on describing specific implementations (e.g., Tavakoli (2000), Thompson (2002), and Vrcelj and Attard (2007)). Little research to date has looked in detail at how the engagement of practitioners affects student learning (e.g., Georgilas et al (2019)). Practitioners may not be familiar with expectations of design courses, for example they may expect complete designs (Tocco and Mata, 2012).…”
Section: Practitioner Tutors In the Design Studiomentioning
confidence: 99%
“…There are several components that affect the creative process such as individual cognitive abilities, personality characteristics and social factors. A study by Georgilas et al (2019) showed that professional practitioner has an impact on the learning process and the delivery from the novices (students), hence negatively affects the creative potential of open-ended projects. Another study showed that adding a professional to student teams did not increase creativity but had a major influence on the selected functions (Zeiler, 2013).…”
Section: 1mentioning
confidence: 99%